2022
DOI: 10.1007/s40670-022-01537-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Academic Performance and Personal Experience Among First-Year Medical Students

Abstract: Background The COVID-19 pandemic forced medical education to rapidly transition from in-person learning to online learning. This change came with learning difficulties, social isolation, limited student/faculty relationships, and decreased academic performance. Objective The purpose of this study is to determine if academic performance, study habits, student/faculty relationships, and mental health were different in first-year medical students (class of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 12 publications
3
31
0
Order By: Relevance
“…However, opposing studies exist. A survey of over 120 medical students from the Kirk Kerkorian School of Medicine in Las Vegas showed that, during the COVID-19 pandemic, first-semester students did not score above the national average as much as first-semester students before the pandemic [ 12 ]. Similarly, a study of over 200 students from Italian universities showed a negative impact of online learning on the concentration and learning abilities of students, two of the strongest predictors of poor academic performance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, opposing studies exist. A survey of over 120 medical students from the Kirk Kerkorian School of Medicine in Las Vegas showed that, during the COVID-19 pandemic, first-semester students did not score above the national average as much as first-semester students before the pandemic [ 12 ]. Similarly, a study of over 200 students from Italian universities showed a negative impact of online learning on the concentration and learning abilities of students, two of the strongest predictors of poor academic performance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…e results reported in the literature are not unanimous; some findings describe negative trends [3] or impacts [4,19] of the pandemic on the academic performance of medical students. On the other hand, there are findings where medical students have stressed the benefits of online lectures [6] and also studies concluding that their cognitive performance remained the same [5] or improved [20].…”
Section: Discussionmentioning
confidence: 99%
“…Examinations have also been transitioned to online or, in some cases, may be deferred. Many students have reported concerns about not being able to learn and practice clinical skills in person ( 44 ). Moreover, there is a decrease in the number of clinical teachers because some of them have devoted their time to pandemic prevention and control teams ( 45 ).…”
Section: Discussionmentioning
confidence: 99%